Integration of complementary and alternative medicine into the healthcare and educational system: Perspectives of healthcare professionals and oncology patients - Racz, Aleksandar; Rukavina, Tomislav; Vasiljev, Vanja; Armano, Andrea; Armano, Ljerka (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the attitudes of healthcare professionals and oncology patients toward integrating complementary and alternative medicine (CAM) into healthcare and education. The aim is to identify differences in perception, acceptance, and interest in CAM education, as well as key challenges and opportunities for its implementation in Croatia. Methods: A cross-sectional study was conducted with 832 respondents (411 patients and 421 healthcare professionals). Standardized questionnaires assessed attitudes, acceptance levels, and the need for further education. Differences between patients and healthcare professionals, as well as between physicians and nurses, were analyzed. Results: Results indicate that patients show higher acceptance of CAM, viewing it as a valuable complement to conventional treatment. Physicians express caution, emphasizing the need for additional education before CAM integration, while nurses are more supportive, reflecting their holistic patient-care approach. Most respondents acknowledge the lack of CAM education in Croatian medical curricula, consistent with international trends. However, a significant number of healthcare professionals express interest in further education, highlighting the need for structured, evidence-based training. In conclusion, findings underscore the necessity of integrating CAM into medical education, developing regulatory frameworks, and implementing structured training programs to ensure safe and informed CAM use in healthcare.